The Role Of Online Social Media PT. BPR Bhakti Daya Economy On Prospective Customers' Decisions To Use Credit Products - Dimas Helmi Saputra; Sumadi, Sumadi (International Journal of Education, Vocational and Social Science, 2024)
This research was conducted as a form of implementation of the final internship assignment carried out by the author. This research examines the role of social media from PT. BPR Bhakti Daya Ekonomi on prospective customers' decisions to use credit products. The focus of this research is to analyze how far social media can provide education regarding credit products in influencing potential customers' decisions to use these products. This research uses a qualitative approach using interviews. Information and data collection is carried out through sources who are the analysis unit of the company in order to represent the company in providing data and information related to the research topic. The research results show that social media such as Instagram and WhatsApp are very useful for expanding market share because of the ease of communication. Digital marketing provides great benefits in building brand image and increasing sales. However, PT. BPR Bhakti Daya Ekonomi has not maximized the use of social media for marketing, which is still limited to WhatsApp and Instagram, thereby limiting market reach. Marketing content is also less interesting, reducing consumer buying interest. However, PT. BPR Bhakti Daya Ekonomi has a great opportunity to develop credit product marketing by increasing content creativity and utilizing technological developments.